Digital camera design - Teh, Sow Boon. (2009)
Stars have been treated as a celestial reference in navigation since ancient time. The constellation scattered over the sky tells lot information to us if it is properly analysed. This concept has been adopted in star camera which is mounted on spacecraft for executing attitude determination in outer space. Star camera captures the image of stars which fall within its field of view. Subsequently, this image will be matched by performing star pattern recognition with the star catalogues stored in the firmware. Lastly, the attitude information of the spacecraft can be computed from the matched star pattern. In short, star camera is just like a usual digital camera with extra value-added function in attitude determination. Digital camera has been evolved through different stages since its invention. Nowadays, CMOS technology is under a well-controlled stable process which eventually emerges to be the baseline process for almost all logic and microprocessors. This has paved the way for Active-Pixel-Sensor (APS) imager to be fabricated on much cheaper and more available manufacturing lines. Hence, APS imager was opted as the candidate image sensor in this project due to its low-power consumption, low cost, low weight and small dimension nature. In addition, these prominent features are fulfilling the trend of microsatellite towards the lighter instrumentation and less power consumption. The main task in this project is to design an optical system for the selected APS imager i.e. OV3630 image sensor from OmniVision Technologies. The aim of the design is to design a high speed lens with desirable high optical performances. ZEMAX optical system design program has been used to design, optimise, and evaluate the desired lens system. A study on OV3630 image sensor has been carried out and summarised so that it provides a platform for future interface-designs. Besides that, the possible attainable Star Magnitude of the proposed lens design has been calculated based on the sensor’s sensitivity. By referring to the calculated Star Magnitude, we are able to predict the limit of the dimmest star which can be captured by the star camera.